In vitro hydrolysis and magnesium release of poly(d, l‐lactide‐co‐glycolide)‐based composites containing bioresorbable glasses and magnesium hydroxide. Issue 41 (15th July 2015) - Uppstu, Peter; Paakki, Charlotta; Rosling, Ari
ABSTRACT Magnesium is important for both bone growth and cartilage formation. However, the postoperative intake of antibiotics such as quinolones may cause a reduction in magnesium levels in tissue. The addition of magnesium to scaffolds may therefore be beneficial for the regeneration of osteochondral defects. In this study, porous composite scaffolds were produced by gas foaming of poly(d, l‐lactide‐co‐glycolide) (PLGA) rods with magnesium‐containing bioresorbable glasses and magnesium hydroxide as fillers. The in vitro hydrolytical degradation of the composite scaffolds in Tris buffer was followed over a 10‐week period. Mg2+ was released in a controlled manner from the scaffolds with varying release profiles between the different materials. Higher glass content resulted in a reduced mass loss compared to scaffolds with lower glass content. As a result of the foaming method, the scaffolds shrank initially, without evidence that the addition of hydrophilic fillers would decrease the initial shrinkage. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42646.